2017
DOI: 10.1126/science.aal5081
|View full text |Cite
|
Sign up to set email alerts
|

Osteoblasts remotely supply lung tumors with cancer-promoting SiglecFhighneutrophils

Abstract: Bone marrow-derived myeloid cells can accumulate within tumors and foster cancer outgrowth. Local immune-neoplastic interactions have been intensively investigated, but the contribution of the systemic host environment to tumor growth remains poorly understood. Here, we show in mice and cancer patients ( = 70) that lung adenocarcinomas increase bone stromal activity in the absence of bone metastasis. Animal studies reveal that the cancer-induced bone phenotype involves bone-resident osteocalcin-expressing (Ocn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
269
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 299 publications
(290 citation statements)
references
References 83 publications
19
269
1
1
Order By: Relevance
“…87 ), can affect bone marrow myeloid progenitor expansion, thus leading to enhanced release of myeloid cells into circulation, and ultimately affect the number of circulating and tumor-infiltrating immunosuppressive myeloid cells and contribute to more severe disease and greater metastatic burden 74,88 . Tumor-induced systemic factors can affect the bone marrow and in turn promote tumor infiltration of cancer-promoting immune components, including neutrophils 89 , monocytes 90 and platelets 91 .…”
Section: The Contribution Of Systemic Factors To the Timementioning
confidence: 99%
“…87 ), can affect bone marrow myeloid progenitor expansion, thus leading to enhanced release of myeloid cells into circulation, and ultimately affect the number of circulating and tumor-infiltrating immunosuppressive myeloid cells and contribute to more severe disease and greater metastatic burden 74,88 . Tumor-induced systemic factors can affect the bone marrow and in turn promote tumor infiltration of cancer-promoting immune components, including neutrophils 89 , monocytes 90 and platelets 91 .…”
Section: The Contribution Of Systemic Factors To the Timementioning
confidence: 99%
“…A recent study showed that the newly formed osteoblasts derive from bone marrow endothelial cells when those are stimulated by metastatic cancer cells [63,64]. Engblom and colleagues introduce a new concept: osteoblasts can be remotely activated by tumor cells remotely even when those are not present in the bone [42]. Future studies will reveal what is the origin of newly formed osteoblasts activated by lung tumor, and whether they are also derived from endothelial cells.…”
Section: Perspectives / Future Directionsmentioning
confidence: 99%
“…Although neutrophils may present pro- or anti-tumoral activity, depending on specific tumor microenvironments [41], we are still far from fully understanding their function in the lung tumor microenvironment, and how this role can be regulated. Now, in an article in Science , Engblom and colleagues reveal the heterogeneity of neutrophils in the lung cancer microenvironment, and that only SiglecF high – expressing neutrophils promote tumor growth [42]. The authors investigated the systemic crosstalk between lung tumor and the bone that regulates the recruitment of pro-tumoral neutrophils by using elegant state-of-the-art techniques, including in vivo sophisticated Cre/loxP technologies in combination with several lung tumor models.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations